THE WORK OF UTKIR HOSHIMOV IS UNIQUE, ARTISTIC LINGUISTIC FEATURES OF LITERARY WORKS (International Conference on Economics, Finance, Banking and Management, 2025)
In this article, Utkir Khoshimov is known not only as a bright star of Uzbek literature, but also as a prose writer, dramatist and public figure who played an important role in modern writing. it is revealed that he chose the method.